A General Strategy for the Synthesis of Functionalised UiO‐66 Frameworks: Characterisation, Stability and CO2 Adsorption Properties. Issue 12 (4th February 2013) - Biswas, Shyam; Van Der Voort, Pascal
Abstract: A general synthetic strategy has been developed, which can be used for the preparation of all the known as well as five new functionalised UiO‐66‐X compounds [X = H, F, F2, Cl, Cl2, Br, Br2, I, CH3, (CH3 )2, CF3, (CF3 )2, NO2, NH2, OH, (OH)2, OCH3, (CO2 H)2, SO3 H, C6 H4 ]. Starting from a reaction mixture of ZrOCl2 · 8H2 O, H2 BDC‐X (BDC: 1, 4‐benzenedicarboxylate), formic acid and N, N ‐dimethylacetamide (DMA) having a molar ratio of 1:1:100:104.44, all the UiO‐66‐X compounds, except UiO‐66‐CO2 H, were obtained under solvothermal conditions (150 °C, 24 h). The phase purity of all the compounds was ascertained by X‐ray powder diffraction (XRPD) analysis, DRIFT spectroscopy and elemental analysis. Determination of lattice parameters from the XRPD patterns of the new thermally activated UiO‐66‐X {X = CF3 (1 ‐CF3 ), (CO2 H)2 [2 ‐(CO2 H)2 ], F2 (3 ‐F2 ), Cl2 (4 ‐Cl2 ), Br2 (5 ‐Br2 )} compounds revealed their structural similarity with the unfunctionalised UiO‐66. Thermogravimetric analyses (TGA) indicate that the five new compounds are stable in the range 290–390 °C in air. Except for3 ‐F2, the new compounds maintain their structural integrity in water, acetic acid and 1M HCl, as verified by XRPD analysis of the samples recovered after suspending them in the respective liquids. As confirmed by N2 and CO2 sorption analyses, all of the new thermally activated compounds exhibit significant microporosity values ( S Langmuir = 217–836 m 2  g –1 ), which are lower than that of the parent UiO‐66. Comparative CO2 sorption studies reveal that the UiO‐66‐X compounds with X = NO2, NH2, OH, CH3 and (CH3 )2 show enhanced CO2 uptake compared to that of the parent compound at 1 bar and 0 °C. Abstract : A general strategy for the preparation of functionalised UiO‐66 frameworks is described. Their CO2 adsorption properties are compared.